Do Not Go Gentle Merce Cunningham's Barbican Events - Winship, Lyndsey (Dance Books Ltd., Alton,Hampshire (UK), 2005)
Merce Cunningham's Barbican Events. Few performances leave you with so much talking material, so many questions about the nature of art, beauty, and what dance is all about. PALABRAS CLAVE: Merce Cunningham, Barbican Events, Event.